Bioderecho, ciencia y tecnología (2020)
This chapter is not about biolaw and what it will be in the XXI century. It is rather the story of the personal involvement of the author in biolaw, of his activity in the field and ofhis recent coming back to law, in general terms, having in mind his fascinating and enriching background at the intersection between science, technology and law. Having spent more than three decades working on the relationship  between law and biomedicine, first, and, then, between law and life sciences, and then between law and science and technologies, the author reaches the conclusion that it does not make a lot of sense to create and cultivate discrete fields oflaw according to specific scientific fields and neither for the all area of technology and law.